A pedagogical framework for engaging middle-aged university faculty in systematic physical culture and health-enhancing activities - Loginov, D.V.; Ponomarev, V.V.; Prikhodov, D.S.; Golm, L.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically substantiate and develop an experimental pedagogical framework for engaging middle-aged university faculty (50–59 years) in systematic physical culture and health-enhancing activities and to recommend it for practical implementation. Methods and structure of the study. At the preliminary stage, a theoretical analysis of scientific-methodological literature was conducted, along with a sociological survey of university faculty regarding their physical culture and health-enhancing activities. The material and technical provision for physical culture among faculty members was assessed, together with the organisational forms and directions of physical culture activities in higher education. The factual material obtained enabled the systematisation and identification of the overall picture of physical culture organisation among university faculty, and the development of the content and structure of an experimental pedagogical framework for motivating educators, including those aged 50–59, to engage in systematic physical culture and sport. Results and conclusions. The comprehensive scientific-theoretical analysis revealed the percentage of the population systematically engaged in physical culture and sport; popular types of physical activity among the population; primary preferences regarding exercise venues; the age distribution of participants in mass physical culture and sporting events; and other relevant factors. Additionally, the structure and content of the experimental pedagogical framework for engaging middle-aged university faculty in systematic physical culture and health-enhancing activities were developed.